Composite aerogel TPE material and preparation method thereof

The composite TPE material with surface-modified silica aerogel and controlled mixing improves thermal insulation and mechanical strength by enhancing dispersion and interface bonding, addressing the limitations of traditional TPE materials in refrigerator seals.

CN120310186APending Publication Date: 2025-07-15CHANGHONG MEILING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510680985.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-26
Publication Date
2025-07-15

AI Technical Summary

Technical Problem

In the scenarios such as the seal strips of refrigeration equipment, existing aerogel/TPE composites have problems such as limited improvement in thermal insulation performance, deterioration of mechanical properties, and high-temperature processing technology to destroy the porous structure of aerogels.

Method used

The composite of surface-modified aerogel with components such as compatibility agents, plasticizers, and antioxidants is adopted to form a gradient interface layer and a nano-scale insulating layer through a step-by-step kneading process to improve the interface bond strength and pore structure integrity.

Benefits of technology

Significantly reduce the thermal conductivity of composite materials, maintain the performance stability and mechanical properties of the materials in a wide temperature range, and adapt to the needs of high-end thermal insulation sealing scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005419250730000111
    Figure BDA0005419250730000111
Patent Text Reader

Abstract

The invention provides a composite aerogel TPE material and a preparation method thereof, the composite aerogel TPE material comprises the following components by weight: 100 parts of a thermoplastic elastomer, 5-35 parts of surface modified aerogel, 3-9 parts of a compatilizer, 10-35 parts of a plasticizer, 0.3-4 parts of an antioxidant, and 1-5 parts of an organic auxiliary agent; the surface modified aerogel is at least one of mesoporous SiO2 aerogel modified by amination or carboxylation. According to the composite TPE material, the addition amount of pure aerogel particles in the TPE is increased by utilizing the surface modified aerogel and the compatilizer, so that the heat conductivity coefficient of the composite TPE material is reduced; meanwhile, the step-by-step mixing process ensures the pore structure of the modified aerogel and ensures the heat insulation function of the aerogel material in the TPE.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of materials technology, and particularly to a composite aerogel TPE material and a preparation method thereof. Background Art

[0002] Thermoplastic elastomer (TPE) is a type of polymer material that combines the elasticity of rubber and the processing characteristics of plastics. Due to its recyclability, simple processing technology (such as extrusion, compression molding, etc.), and excellent flexibility, it is widely used in fields such as home appliances, automobiles, and electronics. In the field of refrigeration appliances, TPE has become a commonly used material for the sealing strips of refrigerators, freezers, and other equipment due to its good sealing performance and low-temperature resistance. However, the thermal conductivity of traditional TPE materials is relatively high (usually 0.2 - 0.3 W / m·K). In scenarios that require high thermal insulation performance (such as the thermal insulation and sealing of refrigerator door gaskets), its thermal insulation effect is difficult to meet the requirements of energy conservation and performance improvement.

[0003] The prior art has attempted to introduce aerogel into TPE-based composites. Aerogel is an ultra-light material with a nano-porous network structure, and its thermal conductivity is as low as 0.013 - 0.025 W / m·K, which can theoretically significantly reduce the heat conduction of the composite material. However, in practical applications, the following bottlenecks are faced: on the one hand, aerogel itself is brittle and difficult to form alone, and it needs to be used in combination with a polymer matrix; on the other hand, traditional composite processes (such as melt blending) have problems such as uneven dispersion of aerogel and poor interfacial bonding force with the TPE matrix, resulting in a significant decline in the mechanical properties of the composite material (such as the tensile strength decreasing by more than 30%). In addition, high-temperature processing processes (such as extrusion temperatures exceeding 190°C) are likely to damage the porous structure of aerogel, further weakening its thermal insulation performance.

[0004] The uneven dispersion of aerogel in the matrix results in limited improvement in thermal insulation performance; the insufficient interfacial bonding force between aerogel and the TPE matrix leads to deterioration of mechanical properties; high-temperature processing processes damage the porous structure of aerogel, further reducing the thermal insulation efficiency, making it difficult for existing aerogel / TPE composites to meet the stringent requirements for the comprehensive performance of materials in scenarios such as refrigeration appliance sealing strips in practical applications. Summary of the Invention

[0005] This application provides a composite aerogel TPE material and a preparation method thereof to solve the problem that existing aerogel / TPE composites are difficult to meet the stringent requirements for the comprehensive performance of materials in scenarios such as refrigeration appliance sealing strips in practical applications.

[0006] In the first aspect, this application provides a composite aerogel TPE material, and the material includes the following components by weight:

[0007] 100 parts of thermoplastic elastomer, 5 - 35 parts of surface - modified aerogel, 3 - 9 parts of compatibilizer, 10 - 35 parts of plasticizer, 0.3 - 4 parts of antioxidant, 1 - 5 parts of organic auxiliary agent; the surface - modified aerogel is at least one of mesoporous SiO₂ aerogels modified by amination or carboxylation.

[0008] In some possible implementation manners, the specific surface area of the surface - modified aerogel is 600 - 800m 2 / g, the pore size distribution is 10 - 50nm, and the grafting rate is 5 - 10wt%.

[0009] In some possible implementation manners, the compatibilizer is maleic anhydride - grafted SEBS (MAH - g - SEBS), the grafting rate is 0.8 - 1.5%, and the mass ratio to the aerogel is 1:3 to 1:5.

[0010] In some possible implementation manners, the plasticizer is a compound system of naphthenic oil and epoxidized soybean oil, the compound mass ratio is 2:1 to 4:1, and the total addition amount does not exceed 25% of the mass of TPE.

[0011] In some possible implementation manners, the organic auxiliary agent includes 0.5 - 2 parts of zinc stearate, 0.5 - 2 parts of calcium stearate, 0.3 - 0.5 parts of organic fluorine - containing surfactant, and 0.5 - 1 part of C5 hydrogenated petroleum resin H5 - 1001.

[0012] In some possible implementation manners, the antioxidant is 1010, pentaerythritol tetrakis [β - (3,5 - di - tert - butyl - 4 - hydroxyphenyl) propionate].

[0013] In some possible implementation manners, the modification process of the mesoporous SiO₂ aerogel modified by amination is as follows:

[0014] The aerogel is vacuum - dried at 80 - 90°C for 6 - 10h;

[0015] The dried aerogel is reacted with a 5wt% ethanol solution of silane coupling agent APTES at a mass ratio of 1:10, refluxed at 60 - 70°C for 4 - 5h to obtain a reflux solution;

[0016] After centrifugal washing of the reflux solution, it is vacuum - dried at 60 - 70°C for 12h to obtain the mesoporous SiO₂ aerogel modified by amination.

[0017] In some possible implementation manners, the thermoplastic elastomer is a styrenic thermoplastic elastomer, the hardness of the thermoplastic elastomer is 68 - 72A, the tensile strength ≥ 11MPA, and the elongation at break ≥ 300%; the melt index of the thermoplastic elastomer is 1 - 5g / 10min, and the density of the thermoplastic elastomer is 0.86 - 0.92g / cm 3 .

[0018] In a second aspect, the present application provides a method for preparing the aerogel composite TPE material described in the first aspect. The method includes:

[0019] Vacuum-dry the aerogel at 60 - 80 °C for 4 - 6 h;

[0020] Premix the thermoplastic elastomer with 50% plasticizer and compatibilizer in a mixer at 160 - 180 °C for 3 - 5 min;

[0021] Add the plasticizer and aerogel to the mixer in 2 - 3 portions, with a mixing temperature of 165 - 175 °C and a total time of 10 - 15 min; add an antioxidant and mix until torque balance to obtain a slurry;

[0022] Obtain the aerogel composite TPE material by twin-screw extrusion or compression molding of the slurry, where the extrusion temperature is controlled at 160 - 200 °C.

[0023] In some possible implementations, the method further includes: the mixing process is carried out under nitrogen protection with an oxygen content < 100 ppm; and the aspect ratio (L / D) of the twin-screw extruder is ≥ 36, and the screw speed is 150 - 200 rpm.

[0024] In a third aspect, the present application provides the use of the aerogel composite TPE material described in the first aspect or the aerogel composite TPE material prepared in the second aspect in the sealing strip of a refrigeration appliance, where the refrigeration appliance includes but is not limited to refrigerators, freezers, display cabinets, and other refrigeration appliances.

[0025] As can be seen from the above, the present application provides a composite aerogel TPE material and a preparation method thereof. The composite aerogel TPE material includes the following components by weight: 100 parts of thermoplastic elastomer, 5 - 35 parts of surface-modified aerogel, 3 - 9 parts of compatibilizer, 10 - 35 parts of plasticizer, 0.3 - 4 parts of antioxidant, and 1 - 5 parts of organic auxiliary agent; the surface-modified aerogel is at least one of mesoporous SiO2 aerogels modified by amination or carboxylation. The present application uses surface-modified aerogel and compatibilizer to increase the addition amount of pure aerogel particles in the thermoplastic elastomer TPE, thereby reducing the thermal conductivity of the composite TPE material; at the same time, the step-by-step mixing process ensures the pore structure of the modified aerogel and ensures the heat insulation function of the aerogel material in TPE. Detailed implementation manners

[0026] Thermoplastic elastomer (TPE) is a type of polymer material that combines the elastic properties of rubber and the processing characteristics of plastics. Due to its recyclability, simple processing techniques (such as extrusion, compression molding, etc.), and excellent flexibility, it is widely used in fields such as household appliances, automobiles, and electronics. In the field of refrigeration appliances, TPE has become a commonly used material for the sealing strips of refrigerators, freezers, and other equipment due to its good sealing performance and low-temperature resistance. However, traditional TPE materials have a relatively high thermal conductivity (usually 0.2 - 0.3 W / m·K), and in scenarios where high thermal insulation performance is required (such as the thermal insulation and sealing of refrigerator door gaskets), their thermal insulation effect is difficult to meet the requirements of energy conservation and performance improvement.

[0027] Existing technologies have attempted to introduce aerogels into TPE-based composites. Aerogel is an ultra-light material with a nano-porous network structure, and its thermal conductivity is as low as 0.013 - 0.025 W / m·K, which theoretically can significantly reduce the heat conduction of the composite material. However, in practical applications, the following bottlenecks are faced: on the one hand, aerogels are brittle and difficult to form alone, and need to be used in combination with a polymer matrix; on the other hand, traditional composite processes (such as melt blending) have problems such as uneven dispersion of aerogels and poor interfacial bonding force with the TPE matrix, resulting in a significant decrease in the mechanical properties of the composite material (such as the tensile strength decreasing by more than 30%). In addition, high-temperature processing techniques (such as extrusion temperatures exceeding 190°C) are likely to damage the porous structure of aerogels, further weakening their thermal insulation performance.

[0028] The uneven dispersion of aerogels in the matrix leads to limited improvement in thermal insulation performance; the insufficient interfacial bonding force between aerogels and the TPE matrix results in the deterioration of mechanical properties; the high-temperature processing technique damages the porous structure of aerogels, further reducing the thermal insulation efficiency, making it difficult for existing aerogel / TPE composites to meet the stringent requirements for the comprehensive performance of materials in scenarios such as refrigeration appliance sealing strips in practical applications.

[0029] Based on this, the present application provides a composite aerogel TPE material, and the material includes the following components by weight:

[0030] 100 parts of thermoplastic elastomer, 5 - 35 parts of surface-modified aerogel, 3 - 9 parts of compatibilizer, 10 - 35 parts of plasticizer, 0.3 - 4 parts of antioxidant, 1 - 5 parts of organic auxiliary agent; the surface-modified aerogel is at least one of mesoporous SiO2 aerogels modified by amination or carboxylation.

[0031] By adjusting the types and dosages of components such as surface-modified aerogel, compatibilizer, and plasticizer in the composite aerogel TPE material, the material properties can be precisely controlled: the addition amount and modification type of the surface-modified aerogel directly affect the heat insulation effect and interfacial bonding strength. A low addition amount takes into account flexibility, while a high addition amount achieves extreme heat insulation. Amination / carboxylation modification is respectively suitable for high-fill and transparent scenarios; the dosage of the compatibilizer determines the dispersibility of the aerogel and the mechanical retention rate. A high dosage can maintain the strength when the aerogel is highly filled; the dosage and compounding ratio of the plasticizer regulate the rigidity and flexibility of the material and its processing adaptability. A low dosage improves the supportability, while a high dosage enhances the flexibility; antioxidants and organic additives (such as zinc stearate, fluorinated surfactants, etc.) optimize the aging resistance and processing efficiency. Under the synergistic effect of multiple components, the material can maintain stable performance in the wide temperature range from -40°C to 120°C, while achieving flexible cost control and green recyclability, meeting the different requirements for heat insulation, mechanics, and processability in fields such as refrigeration and automobiles.

[0032] In some embodiments, the specific surface area of the surface-modified aerogel is 600 - 800 m 2 / g, the pore size distribution is 10 - 50 nm, and the grafting rate is 5 - 10 wt%.

[0033] Selecting a surface-modified aerogel with a super-large specific surface area of 600 - 800 m 2 / g can provide abundant surface active sites, enabling a single aerogel particle to adsorb more compatibilizer molecules, forming a gradient interfacial layer of "aerogel - compatibilizer - TPE matrix", reducing the dispersion particle size of the aerogel in TPE from 500 nm in the traditional process to below 100 nm, avoiding the heat conduction path formed by aggregates, and thus improving the thermal conductivity.

[0034] By matching the pore size of the surface-modified aerogel with the infrared thermal radiation wavelength (2.5 - 20 μm), infrared heat conduction is blocked through the photon scattering effect. At the same time, the static air in the pores forms a nano-scale adiabatic layer (the thermal conductivity of air is 0.026 W / m·K). The dual mechanism reduces the thermal conductivity of the composite material to 0.08 - 0.12 W / m·K, a 60% reduction compared to pure TPE.

[0035] Amino groups (-NH2) are introduced through the silane coupling agent APTES, and an esterification reaction occurs with the maleic anhydride group (-MAH) of the compatibilizer MAH-g-SEBS to form chemical covalent bonds, increasing the interfacial bonding strength by 3 times. When the addition amount of the aerogel reaches 24 parts, the tensile strength retention rate of the composite material is still > 85%, and the elongation at break remains at 620%, solving the problem of "mechanical deterioration caused by high filling" in the traditional process.

[0036] For surface-modified aerogels, appropriate grafting is selected to avoid the collapse of the aerogel skeleton caused by excessive functionalization. In the step-by-step mixing process, the pore retention rate can reach 92%, and the specific surface area retention rate > 95%, ensuring the inherent heat insulation performance of the aerogel (effectively transferred to the composite material).

[0037] The amino groups of the aminated aerogel can inhibit the oxidative chain scission of the TPE matrix at high temperatures (120 °C). In combination with the antioxidant system, the thermal conductivity fluctuation of the material is < 10% in the range of -40 °C to 120 °C, and the tensile strength retention rate > 80%, adapting to the complex environment from the refrigerator freezer compartment (-18 °C) to the compressor compartment (80 °C).

[0038] Mesoporous SiO2 aerogels modified by amination or carboxylation with a specific surface area of 600 - 800 m 2 / g, pore size distribution of 10 - 50 nm, and grafting rate of 5 - 10 wt% can significantly improve the performance of the composite aerogel TPE material: the high specific surface area provides abundant active sites, achieving nano-scale uniform dispersion through a compatibilizer. Combining the photon scattering of the mesoporous structure and the air adiabatic effect, the thermal conductivity is as low as 0.08 - 0.12 W / m·K, a 60% reduction compared to pure TPE; amination modification strengthens the interfacial bonding through covalent bonds, and the tensile strength retention rate > 85% at high filling amounts. Carboxylation modification improves the compatibility and processing efficiency at low filling amounts through hydrogen bonds; an appropriate grafting rate ensures that the pore retention rate of the aerogel reaches 92%, maintaining long-term heat insulation; the material has stable performance in the wide temperature range of -40 °C to 120 °C, can be recycled more than 3 times and meets environmental protection regulations, and has the advantages of ultra-low thermal conductivity, high flexibility, and weather resistance and deformation resistance, suitable for high-end heat insulation and sealing scenarios.

[0039] In some embodiments, the compatibilizer is maleic anhydride grafted SEBS (MAH-g-SEBS) with a grafting rate of 0.8 - 1.5% and a mass ratio to the aerogel of 1:3 to 1:5.

[0040] The density of maleic anhydride (-MAH) groups matches the active sites of amino / carboxyl groups on the aerogel surface, forming chemical covalent bonds through an esterification reaction, and the interfacial bonding strength is increased by more than 3 times compared to physical blending. The mass ratio of the compatibilizer to the aerogel of 1:3 to 1:5 ensures that the aerogel surface is fully coated with MAH-g-SEBS, forming a "aerogel-compatibilizer-TPE" core-shell structure, and the dispersed particle size is reduced from 500 nm in the traditional process to below 100 nm, avoiding the formation of heat conduction paths by aggregates.

[0041] Select maleic anhydride grafted SEBS (MAH-g-SEBS) with a grafting rate of 0.8 - 1.5% as the compatibilizer, and control the mass ratio with the aerogel at 1:3 to 1:5, which can bring significant beneficial effects: The maleic anhydride groups form chemical covalent bonds with the amino / carboxyl groups on the aerogel surface through esterification reaction, and the interfacial bonding strength is increased by more than 3 times. When the aerogel addition amount reaches 24 parts, the tensile strength retention rate of the composite material can still be > 85%, and the elongation at break can be maintained at 620%; this ratio ensures that the aerogel surface is fully coated by the compatibilizer, forming a core-shell structure and achieving nano-scale uniform dispersion (particle size < 100nm), with a thermal conductivity as low as 0.08W / m·K, which is 66% lower than that of pure TPE; the chemical structure of the compatibilizer is similar to that of the TPE matrix, and it can be dispersed at a low temperature of 160 - 180°C. With nitrogen protection, the pore retention rate of the aerogel can reach 92%, effectively protecting the mesoporous structure; in addition, the material can be recycled and processed more than 3 times, with a performance decline of < 15%, and it meets environmental protection standards, having the advantages of high-efficiency heat insulation, mechanical stability, low-temperature processing adaptability, and environmental friendliness.

[0042] In some embodiments, the plasticizer is a compound system of naphthenic oil and epoxidized soybean oil, and the compound mass ratio is 2:1 to 4:1, and the total addition amount does not exceed 25% of the mass of TPE.

[0043] When the proportion of naphthenic oil is 67% - 80%, the glass transition temperature of the TPE matrix can be reduced to -50°C, so that the material can still maintain softness in low-temperature environments such as the refrigerator freezer (-18°C), and the elongation at break can reach more than 800%, avoiding hardening and cracking of the sealing strip.

[0044] The proportion of epoxidized soybean oil is 20% - 33%. Through the hydrogen bond interaction between the ester group and the hydroxyl group on the aerogel surface, the compatibility of the plasticizer with the matrix / filler is improved, and the "migration and exudation phenomenon" is inhibited. When the total addition amount reaches 25%, the compression set of the material is only 8% (the traditional single plasticizer system > 15%), and the sealing performance is stable during long-term use.

[0045] The ester group (-COO-) of epoxidized soybean oil forms a dipole-dipole interaction with the amino group (-NH2) of the aminated aerogel, so that the plasticizer forms a "lubricating layer" on the aerogel surface, reducing the mixing torque by 15% - 20%, and at the same time promoting the dispersion of the aerogel (the particle size is reduced from 200nm to 150nm), further increasing the reduction rate of the thermal conductivity (a further 5% reduction compared to the pure naphthenic oil system).

[0046] The polarity difference of the compound system forms a "microphase dispersion structure". Naphthenic oil penetrates between the TPE molecular chains to reduce stiffness, and epoxidized soybean oil adsorbs on the aerogel surface to form steric hindrance. The two work together to prevent the aggregation of aerogel particles due to van der Waals forces. Especially when the aerogel addition amount > 20 parts, the dispersion uniformity is increased by 30%.

[0047] The viscosity of the compound plasticizer is lower than that of single epoxidized soybean oil, enabling rapid melting at low temperatures. In combination with the strong shear environment of a twin-screw extruder with a length-diameter ratio ≥ 36, it ensures the mixing uniformity at a high aerogel filling amount (such as 24 parts), avoiding the damage to the aerogel pores by traditional high-temperature processes (> 190°C) (the pore retention rate is maintained at 92%).

[0048] Epoxidized soybean oil is a bio-based material (derived from the deep processing of soybean oil), with a biodegradable component ratio > 60%, meeting the EU EN 13432 standard; the compound system has no aromatic solvents, the volatile content < 0.5%, and it has excellent stability during recycling and processing (the plasticizer migration rate < 5% after 3 times of recycling), meeting the requirements of green manufacturing.

[0049] In some embodiments, the organic additives include 0.5 - 2 parts of zinc stearate, 0.5 - 2 parts of calcium stearate, 0.3 - 0.5 parts of organic fluorinated surfactant, and 0.5 - 1 part of C5 hydrogenated petroleum resin H5-1001.

[0050] Zinc ions in zinc stearate molecules form a weak coordination interaction with the TPE matrix and are uniformly dispersed between molecular chains as an internal lubricant, reducing the internal friction of the melt, decreasing the mixing torque by 15% - 20%, and simultaneously enhancing the melt fluidity. Calcium stearate (CaSt2) has a stronger polar calcium metal and tends to migrate to the melt surface to form an external lubricating film, which can reduce the interfacial friction coefficient between the material and processing equipment (such as screws and molds) (from 0.4 to 0.25), reducing the melt fracture phenomenon, especially suitable for the extrusion of thin-walled products.

[0051] When ZnSt2 and CaSt2 are compounded (mass ratio 1:1), the internal lubrication reduces the melt viscosity, and the external lubrication reduces surface defects, enabling the composite material to achieve uniform dispersion at a low shear rate and avoiding pore damage of the aerogel caused by high shear force.

[0052] The long-chain alkyl group of the stearate root (C 17 H 35 COO - ) physically adsorbs and coats the surface of the aerogel, reducing its surface energy, decreasing the dispersion particle size of the aerogel in the TPE matrix from 200 nm to below 120 nm. At the same time, through the weak bonding (such as hydrogen bonds or ionic bonds) between metal ions (Zn 2+ / Ca 2+ ) and the surface hydroxyl groups (-OH) of the aerogel, a "bridge layer of additives" is formed to enhance the interfacial bonding strength.

[0053] The fluorocarbon chain (-CF2-) of the fluorosurfactant has an ultra-low surface energy (<15 mN / m), preferentially adsorbs on the surface of the aerogel to form a "fluorine coating layer", reduces the interfacial tension between aerogel particles to below 0.5 mN / m, inhibits agglomeration through the entropy repulsion effect, and achieves nanoscale dispersion (particle size <80 nm). Actual measurements show that when 0.5 parts of this surfactant are added, the dispersion uniformity index (UI value) of the aerogel in TPE increases from 0.68 to 0.92 (UI = 1 means completely uniform).

[0054] The fluorocarbon chains are oriented on the material surface to form a hydrophobic barrier, increasing the surface contact angle of the composite material from 85° to over 135° and reducing the water absorption rate from 0.8% to below 0.2%. It is especially suitable for thermal insulation applications in humid environments (such as humidity >85%), avoiding the increase in thermal conductivity caused by water absorption of the aerogel (the thermal conductivity can increase by 30%-50% after water absorption).

[0055] The low surface energy property reduces the adhesion of pollutants such as dust and oil stains. At the same time, the chemical inertness of the fluorocarbon chain improves the chemical corrosion resistance of the material and extends its service life.

[0056] C5 hydrogenated petroleum resin (mainly composed of hydrogenated cyclopentadiene polymer) has both a non-polar alicyclic structure (compatible with the ethylene-butene segment of SEBS) and trace polar groups (such as allyl hydroxyl groups remaining during the hydrogenation process), and can simultaneously form physical entanglement and hydrogen bond interactions with the TPE matrix and the surface of the aerogel (such as hydroxylated aerogel), increasing the interfacial adhesion strength by 25%-30%.

[0057] The rigid cyclic structure of the resin serves as a physical crosslinking point, restricting the excessive slippage of TPE molecular chains, significantly increasing the tensile strength of the composite material (from 10 MPa to 13 MPa) and the tear strength (from 25 kN / m to 32 kN / m), while maintaining an elongation at break ≥600% (800% for the pure TPE system), achieving a performance balance of "rigidity and flexibility".

[0058] The resin acts as a viscosity-increasing agent in the molten state (150 - 170 °C) to reduce the melt elasticity and reduce the die swell phenomenon, improving the forming accuracy of complex-shaped products.

[0059] In some embodiments, the antioxidant is pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0060] Antioxidant 1010 (pentaerythritol tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]) is a hindered phenol antioxidant containing multiple hindered phenol structures in its molecule. When the material generates free radicals (such as alkyl radicals RO and alkoxy radicals ROO) under the action of heat, light, mechanical stress or chemical action, the phenolic hydroxyl group (-OH) of antioxidant 1010 will react with free radicals preferentially, generating stable phenoxy radicals through hydrogen atom transfer, thus terminating the free radical chain reaction and preventing the spread of oxidative degradation.

[0061] Hydroperoxides (ROOH) generated during the oxidation process of the material will accelerate degradation. Antioxidant 1010 can react with hydroperoxides through its own structure, decompose them into stable non-reactive products, and reduce the "fuel" for the oxidation chain reaction. Under high-temperature processing (such as extrusion and molding) or long-term high-temperature use environments, antioxidant 1010 can effectively inhibit the thermal oxidation reaction of the material, delay aging phenomena such as molecular chain breakage and crosslinking, and maintain the mechanical properties (such as tensile strength and elasticity) and appearance (such as color and gloss) of the material.

[0062] Antioxidant 1010 prevents the degradation of the polymer matrix due to oxidation during the preparation process of aerogel (such as high-temperature crosslinking and solvent evaporation), ensures the integrity of the aerogel skeleton structure, and avoids pore collapse or a decrease in mechanical properties.

[0063] In processing steps such as mixing and extrusion, it reduces the melt viscosity fluctuations or crosslinking phenomena generated by the oxidation of the polymer, makes the processing process more stable, and improves the forming quality and consistency of aerogel products.

[0064] Antioxidant 1010 can be used in combination with sulfur-containing auxiliary antioxidants (such as thioesters) or hindered amine light stabilizers (HALS), and synergistically inhibits oxidation and photoaging through the "primary - auxiliary antioxidant mechanism" to further enhance the comprehensive durability of the material.

[0065] In some embodiments, the modification process of the aminated mesoporous SiO2 aerogel is as follows:

[0066] The aerogel is vacuum dried at 80 - 90 °C for 6 - 10 h;

[0067] The dried aerogel is reacted with a 5 wt% ethanol solution of silane coupling agent APTES at a mass ratio of 1:10, and refluxed at 60 - 70 °C for 4 - 5 h to obtain a reflux solution;

[0068] The reflux solution is centrifuged and washed, and then vacuum dried at 60 - 70 °C for 12 h to obtain the aminated mesoporous SiO2 aerogel.

[0069] The residual solvent and moisture in the pores of the aerogel were removed by vacuum drying at 80 - 90 °C for 6 - 10 hours to activate the surface silanol (-SiOH) active sites, laying the foundation for subsequent modification reactions. Subsequently, the dried aerogel and a 5wt% ethanol solution of the silane coupling agent APTES were refluxed at 60 - 70 °C for 4 - 5 hours in a mass ratio of 1:10. The ethoxy groups of APTES were hydrolyzed into silanol groups and condensed with the surface silanol groups of the aerogel to form Si-O-Si covalent bonds, grafting amino groups (-NH2) onto the surface of the aerogel, introducing strongly polar active groups, significantly enhancing the surface chemical activity, improving the interfacial compatibility with the organic matrix, and enhancing the interfacial binding force of the composite material through hydrogen bonding or chemical cross-linking. Finally, centrifugal washing was used to remove the unreacted APTES and by-products, and vacuum drying at 60 - 70 °C for 12 hours was carried out to fix the grafted structure and activate the amino groups to ensure the reaction activity of the amino groups. This process converted the surface of the aerogel from hydrophilic to weakly polar, enabling the selective adsorption of polar molecules, strengthening the nano-network structure to improve the thermal stability and mechanical strength.

[0070] In some embodiments, the thermoplastic elastomer is a styrene-based thermoplastic elastomer, the hardness of the thermoplastic elastomer is 68 - 72A, the tensile strength ≥ 11 MPA, and the elongation at break ≥ 300%; the melt index of the thermoplastic elastomer is 1 - 5 g / 10 min, and the density of the thermoplastic elastomer is 0.86 - 0.92 g / cm 3 。

[0071] Thermoplastic elastomers (TPEs) with a high melt index have significant processing performance advantages. They have excellent fluidity and low melt viscosity in the molten state, facilitating rapid mold filling and the formation of complex structures. They are suitable for processes such as injection molding of thin-walled products, blown film, or casting. Moreover, they have a low processing temperature and a wide processing temperature range, which can reduce the risk of high-temperature degradation and energy consumption, and are also easily compounded with other materials through processes such as co-injection molding and overmolding. In terms of molecular structure, such materials usually have a relatively low average molecular weight, a low degree of branching, or a linear structure, and some will improve the fluidity by adding processing aids.

[0072] The hardness of the thermoplastic elastomer being 68 - 72A indicates that the material belongs to the category of soft elastomers, combining the flexibility of rubber and the processability of plastics. For example, when used in composite materials, it can buffer external stresses, reduce brittle cracking, and maintain shape stability. And when its tensile strength ≥ 11 MPa and elongation at break ≥ 300%, it is not easily broken under stress and can withstand large deformations (such as tensile and compression cycles). Typical applications include:

[0073] The melt index of the thermoplastic elastomer being 1 - 5 g / 10 min indicates that the material has a relatively low fluidity in the molten state, making it suitable for processing techniques that require shape retention (such as extrusion molding and injection molding of thick-walled products). Combining with the thermoplastic characteristics of styrenic elastomers, materials with a low melt index are not prone to excessive degradation at high temperatures and can be compatible with various processing equipment (such as traditional plastic extruders), reducing the complexity of the production process.

[0074] The density of the thermoplastic elastomer is close to that of polyolefins (PE, PP), facilitating blending and modification with other resins (such as making composite materials by adding 30% - 50% proportion), avoiding problems such as delamination or sedimentation caused by density differences, and improving the uniformity of the system.

[0075] Polar groups (such as -COOH, -OH) can be introduced into the styrene segments in the molecular chains of the thermoplastic elastomer through reactions such as halogenation and grafting, enhancing the interfacial bonding force with inorganic fillers (such as modified SiO2 aerogel and calcium carbonate), and improving the mechanical properties and thermal stability of the composite material.

[0076] In some embodiments, the present application provides a method for preparing the aerogel composite TPE material described in the first aspect. The method includes:

[0077] Vacuum-dry the aerogel at 60 - 80 °C for 4 - 6 h;

[0078] Premix the thermoplastic elastomer with 50% plasticizer and compatibilizer in a mixer at 160 - 180 °C for 3 - 5 min;

[0079] Add the plasticizer and aerogel to the mixer in 2 - 3 portions, with a mixing temperature of 165 - 175 °C and a total time of 10 - 15 min; add antioxidant and mix until torque balance to obtain a slurry;

[0080] Obtain the aerogel composite TPE material by double-screw extrusion or compression molding of the slurry, where the extrusion temperature is controlled at 160 - 200 °C.

[0081] The aerogel is first vacuum-dried at 60 - 80 °C for 4 - 6 h to remove surface-adsorbed moisture and small-molecule impurities, avoiding degradation of the thermoplastic elastomer (TPE) or poor interfacial bonding caused by residual moisture during subsequent mixing. Adding the aerogel and plasticizer in 2 - 3 portions, combined with a mixing temperature of 165 - 175 °C and a total time of 10 - 15 min, can reduce aerogel agglomeration through segmented dispersion, utilize the swelling effect of the plasticizer to improve its wettability in the TPE matrix, and form a more uniform nano-dispersed structure, thereby improving the mechanical properties (such as tensile strength and tear resistance) and functionality (such as heat insulation and adsorption capacity) of the composite material.

[0082] Pre - mix 50% plasticizer and compatibilizer in a Banbury mixer at 160 - 180°C for 3 - 5 min first. The plasticizer can fully penetrate between the TPE molecular chains through high - temperature melting, reducing the melt viscosity. At the same time, the compatibilizer (such as maleic anhydride - grafted polymer) improves the interfacial compatibility between TPE and the aerogel surface (containing silanol groups) through chemical bonding or physical entanglement, reducing phase separation, enhancing the flexibility, resilience performance, and overall uniformity of the composite material, and avoiding the deterioration of mechanical properties caused by poor compatibility or material layering during the processing.

[0083] Add antioxidants in the later stage of mixing (when the torque is balanced) to avoid their premature consumption during long - time high - temperature mixing, ensure effective radical capture in the TPE matrix, inhibit oxidative degradation during processing and use, extend the service life of the material, especially suitable for high - temperature extrusion (160 - 200°C) or scenarios of long - term exposure to a thermo - oxidative environment. The dual - process options of twin - screw extrusion or compression molding can adapt to different product requirements: Twin - screw extrusion is suitable for continuous production of long - strip products such as fibers and sheets, achieving stable plasticization and efficient extrusion by precisely controlling the extrusion temperature (160 - 200°C); Compression molding is suitable for products with complex shapes or thick walls, ensuring uniform filling of the aerogel into the mold cavity by applying pressure, reducing bubble or material shortage defects. The segmented mixing and precise temperature control process shortens the total processing time, improves production efficiency, and reduces energy consumption, meeting the trend of green manufacturing.

[0084] By combining the high specific surface area and porous structure of the aerogel with the elastic properties of TPE, the composite material can be directionally endowed with functions such as heat insulation, sound insulation, adsorption, or electromagnetic shielding, while maintaining the recyclability and processing convenience of TPE.

[0085] In some embodiments, the method further includes: the mixing process is carried out under nitrogen protection, and the oxygen content <

[0086] 100 ppm; and the length - to - diameter ratio (L / D) of the twin - screw extruder ≥ 36, and the screw speed is 150 - 200 rpm.

[0087] The low - oxygen environment can significantly reduce the probability of contact between the functional groups on the surface of thermoplastic elastomer (TPE) and the aerogel during high - temperature mixing (165 - 175°C) and extrusion (160 - 200°C), inhibit the breakage, cross - linking of TPE molecular chains or the oxidation of silanol groups on the aerogel surface, thereby maintaining the elastic properties of TPE and the integrity of the porous structure of the aerogel. Especially for styrene - based TPE containing unsaturated double bonds, it can avoid problems such as increased hardness and decreased elasticity caused by oxidation, and prevent the adsorption performance of the aerogel from being damaged due to oxidation, ensuring the stability of the mechanical properties (such as tensile strength, elongation at break) and functionality (such as heat insulation, adsorption) of the composite material during long - term use.

[0088] The twin-screw extruder with an aspect ratio ≥ 36 provides a longer residence time of the material and a more complex screw combination space (such as more refined zoning of the conveying section, compression section, shearing section, and homogenization section). Combining with the strong shear force generated by a high rotational speed of 150 - 200 rpm, it can further break the aerogel particles (nanoscale or micron-scale) and uniformly disperse them in the TPE matrix, reducing the formation of agglomerates. At the same time, the increase in the aspect ratio makes the melting and blending of the plasticizer, compatibilizer, and TPE more sufficient. The compatibilizer forms a more stable transition layer between the TPE and the aerogel through dynamic vulcanization or interfacial reaction, improving the interfacial bonding force between the two phases, thereby enhancing the impact resistance, dimensional stability, and functional uniformity (such as the consistency of the thermal conductivity coefficient) of the composite material.

[0089] The high rotational speed of 150 - 200 rpm speeds up the material conveying rate and mixing frequency, shortening the overall processing cycle. Combining with a lower melt viscosity (low degree of oxidation and less entanglement of molecular chains) under nitrogen protection, a higher extrusion output can be achieved. At the same time, the strong shearing effect enables the amino groups on the surface of the aerogel (modified by APTES) to come into more sufficient contact with the polar groups on the TPE molecular chain (such as ester groups and anhydride groups introduced through the compatibilizer), promoting chemical bonding or physical adsorption to form an "aerogel - TPE - compatibilizer" interpenetrating network structure, which not only enhances the mechanical strength of the composite material but also retains the recyclability of the TPE, meeting the requirements of the circular economy.

[0090] In some embodiments, the present application provides the application of the aerogel composite TPE material in the above embodiments in the sealing strips of refrigeration appliances, where the refrigeration appliances include, but are not limited to, refrigerators, freezers, display cabinets, and other refrigeration appliances.

[0091] Example 1

[0092] Vacuum-dry the aerogel at 60 - 80 °C for 4 - 6 h; premix the thermoplastic elastomer with 50% plasticizer and compatibilizer in a mixer at 160 - 180 °C for 3 - 5 min; add the plasticizer and the aerogel to the mixer in 2 - 3 portions, with a mixing temperature of 165 - 175 °C and a total time of 10 - 15 min; add the antioxidant and mix until the torque is balanced to obtain a slurry; extrude or mold the slurry through a twin-screw extruder to obtain the aerogel composite TPE material, where the extrusion temperature is controlled at 160 - 200 °C.

[0093] Example 2

[0094] The aerogel is vacuum-dried at 60 - 80°C for 4 - 6 h; the thermoplastic elastomer is premixed with 50% plasticizer and compatibilizer in a mixer at 160 - 180°C for 3 - 5 min; the plasticizer and the aerogel are added to the mixer in 2 - 3 portions, the mixing temperature is 165 - 175°C, and the total time is 10 - 15 min; an antioxidant is added and mixed until torque balance is achieved to obtain a slurry; the slurry is processed by twin-screw extrusion or compression molding to obtain an aerogel composite TPE material, where the extrusion temperature is controlled at 160 - 200°C.

[0095] Example 3

[0096] The aerogel is vacuum-dried at 60 - 80°C for 4 - 6 h; the thermoplastic elastomer is premixed with 50% plasticizer and compatibilizer in a mixer at 160 - 180°C for 3 - 5 min; the plasticizer and the aerogel are added to the mixer in 2 - 3 portions, the mixing temperature is 165 - 175°C, and the total time is 10 - 15 min; an antioxidant is added and mixed until torque balance is achieved to obtain a slurry; the slurry is processed by twin-screw extrusion or compression molding to obtain an aerogel composite TPE material, where the extrusion temperature is controlled at 160 - 200°C.

[0097] The specific component information of Examples 1 to 3 is shown in Table 1.

[0098] Table 1

[0099] Component Example 1 Example 2 Example 3 SEBS-based TPE 100 100 100 <![CDATA[Hydrophobic SiO2 aerogel]]> 15 13 24 Compatibilizer 9 7 9 Plasticizer 15 30 16 Antioxidant 0.3 0.2 0.4 Other additives 5 2 3

[0100] Take Example 2 and Example 3, and set up a blank control group (pure TPE material, i.e., the SEBS-based TPE in Example 2), and use a thermal conductivity meter TC3000E to test its thermal conductivity. The test results are shown in Table 2.

[0101] Table 2: Thermal conductivity results of each example and the control group

[0102]

[0103] Analysis: The aerogel composite TPE materials of Example 2 and Example 3 have a significant improvement compared to the control group.

[0104] In this application, by adding aerogel to the traditional TPE material, the thermal conductivity of the material is further reduced. At the same time, through the preparation method of step-by-step mixing of the aerogel modifier, the addition amount of the aerogel is increased and the complex pore structure of the aerogel is retained. This technical solution has the advantages of simple process, low cost, and being suitable for upgrading existing production lines, and can be widely applied to the field of sealing and thermal insulation of refrigerators and other refrigeration equipment.

[0105] As can be seen from the above embodiments, the present application provides a composite aerogel TPE material and a preparation method thereof. The composite aerogel TPE material comprises the following components in parts by weight: 100 parts of thermoplastic elastomer, 5 - 35 parts of surface-modified aerogel, 3 - 9 parts of compatibilizer, 10 - 35 parts of plasticizer, 0.3 - 4 parts of antioxidant, and 1 - 5 parts of organic auxiliary agent; the surface-modified aerogel is at least one of mesoporous SiO2 aerogels modified by amination or carboxylation. The present application improves the addition amount of pure aerogel particles in the thermoplastic elastomer TPE by using the surface-modified aerogel and the compatibilizer, thereby reducing the thermal conductivity of the composite TPE material; at the same time, the step-by-step mixing process ensures the pore structure of the modified aerogel and ensures the heat insulation function of the aerogel material in the TPE.

[0106] For the similar parts between the embodiments provided in the present application, reference can be made to each other. The specific embodiments provided above are only several examples under the general concept of the present application and do not constitute a limitation on the protection scope of the present application. For those skilled in the art, any other embodiments extended based on the solution of the present application without creative efforts belong to the protection scope of the present application.

Claims

1. A composite aerogel TPE material, characterized in that, The material includes the following components by weight: 100 parts of thermoplastic elastomer, 5 - 35 parts of surface - modified aerogel, 3 - 9 parts of compatibilizer, 10 - 35 parts of plasticizer, 0.3 - 4 parts of antioxidant, and 1 - 5 parts of organic auxiliary agent; the surface - modified aerogel is at least one of mesoporous SiO2 aerogels modified by amination or carboxylation.

2. The composite aerogel TPE material according to claim 1, wherein The specific surface area of the surface-modified aerogel is 600 - 800 m 2 / g, the pore size distribution is 10 - 50 nm, and the grafting rate is 5 - 10 wt%.

3. The composite aerogel TPE material according to claim 1, wherein, The compatibilizer is maleic anhydride - grafted SEBS with a grafting rate of 0.8 - 1.5%, and the mass ratio with the aerogel is 1:3 to 1:

5.

4. The composite aerogel TPE material according to claim 1, wherein The plasticizer is a compound system of naphthenic oil and epoxidized soybean oil with a compound mass ratio of 2:1 to 4:1, and the total addition amount does not exceed 25% of the mass of the thermoplastic elastomer.

5. The composite aerogel TPE material according to claim 1, characterized in that, The organic auxiliary agent includes 0.5 - 2 parts of zinc stearate, 0.5 - 2 parts of calcium stearate, 0.3 - 0.5 parts of organic fluorinated surfactant, and 0.5 - 1 part of C5 hydrogenated petroleum resin H5 - 1001.

6. The composite aerogel TPE material according to claim 1, wherein The antioxidant is 1010.

7. The composite aerogel TPE material according to claim 2, wherein The modification process of the aminated mesoporous SiO2 aerogel is as follows: The aerogel is vacuum - dried at 80 - 90°C for 6 - 10 h; The dried aerogel reacts with a 5wt% ethanol solution of silane coupling agent APTES at a mass ratio of 1:10, refluxes at 60 - 70°C for 4 - 5 h to obtain a reflux solution; After centrifugal washing of the reflux solution, it is vacuum - dried at 60 - 70°C for 12 h to obtain the aminated mesoporous SiO2 aerogel.

8. The composite aerogel TPE material according to claim 2, wherein The thermoplastic elastomer is a styrenic thermoplastic elastomer, the hardness of the thermoplastic elastomer is 68 - 72A, the tensile strength ≥ 11 MPA, and the elongation at break ≥ 300%; the melt index of the thermoplastic elastomer is 1 - 5 g / 10 min, and the density of the thermoplastic elastomer is 0.86 - 0.92 g / cm 3 .

9. A method for preparing the aerogel composite TPE material according to any one of claims 1-8, characterized in that, The method includes: The aerogel is vacuum - dried at 60 - 80°C for 4 - 6 h; The thermoplastic elastomer, 50% of the plasticizer, and the compatibilizer are initially mixed in a mixer at 160 - 180°C for 3 - 5 min; The plasticizer and the aerogel are added to the mixer in 2 - 3 times, the mixing temperature is 165 - 175°C, and the total time is 10 - 15 min; the antioxidant is added and mixed until the torque is balanced to obtain a slurry; The slurry is processed by twin - screw extrusion or compression molding to obtain an aerogel - composite TPE material, where the extrusion temperature is controlled at 160 - 200°C.

10. The method according to claim 9, characterized in that The method also includes: the mixing process is carried out under nitrogen protection with an oxygen content < 100 ppm; and the length - to - diameter ratio of the twin - screw extruder is ≥ 36, and the screw speed is 150 - 200 rpm.